The mythistory of Kajir Ronghangpi
1 online resource (348 pages)
Keywords: Mythistory and Memory in Kaziranga explores the cultural and ecological heritage of Kaziranga National Park through the oral traditions of the Karbi people, centering on the mythical figure of Kajir Ronghangpi. Combining indigenous studies, environmental anthropology, and oral history, the book examines how Karbi myths, folktales, and sacred landscapes shape local identity and territorial belonging. It challenges dominant narratives of Kaziranga as an uninhabited wilderness, revealing it instead as a vibrant cultural landscape. Through critical analysis of oral narratives and community memory, the book documents how traditions inform ecological practices and resist modern state-driven conservation discourses. Offering an alternative history of one of India's most iconic national parks, this volume is essential for scholars of folklore, indigenous knowledge systems, cultural geography, and biodiversity conservation.The subject matter of this book includes: Explores the oral history and ecological relationship between the Karbis and Kaziranga National Park. Challenges state-centric narratives by foregrounding community-based knowledge, traditions, and myths. Examines biodiversity, sacred groves, and climate change through the lens of oral traditions. Introduces a legendary female figure as central to the cultural construction of place and heritage. Print edition not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan or Bhutan)